2020
DOI: 10.1016/j.jhin.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and transmission dynamics of COVID-19 in healthcare workers at a London teaching hospital

Abstract: Background Healthcare worker (HCW)-associated coronavirus disease 2019 (COVID-19) is of global concern due to the potential for nosocomial spread and depletion of staff numbers. However, the literature on transmission routes and risk factors for COVID-19 in HCWs is limited. Aim To examine the characteristics and transmission dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in HCWs in a university teaching hospital in London, UK. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 10 publications
10
74
0
2
Order By: Relevance
“…The authors therefore concluded that the patterns observed were consistent with multiple introductions into the hospitals through community-acquired infections. Similarly, studies are pointing to community transmission dynamics and public policies (e.g., universal mask-wearing) as the main drivers of HCWs infection (161)(162)(163).…”
Section: How Do We Explain the High Infection Rate Among Hcws Despitmentioning
confidence: 99%
“…The authors therefore concluded that the patterns observed were consistent with multiple introductions into the hospitals through community-acquired infections. Similarly, studies are pointing to community transmission dynamics and public policies (e.g., universal mask-wearing) as the main drivers of HCWs infection (161)(162)(163).…”
Section: How Do We Explain the High Infection Rate Among Hcws Despitmentioning
confidence: 99%
“…In particular, the administrative staff of hospitals, ambulatory and medical universities belong to the mentioned group. Possibly, the lack of appropriate medical education as well as increased exposition of this group to infectious material makes them one of the possible infectious vectors, including SARS-CoV-2 [ 4 , 12 , 13 ]. Moreover, the level of vaccination coverage among HCW for other infectious diseases like flu, rubella, tetanus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of HCWs working in outpatient clinics among all infected HCWs is reported to be as low as 2.7%–6.9%. 4 9 The brief interaction time, low rate of performing aerosol-generating procedures, and low frequency of direct contact in outpatient clinics could be possible reasons for the low transmission rate of COVID-19 in such settings. Previous studies have reported that using N95-equivalent masks and face shields were associated with lower transmission rate.…”
mentioning
confidence: 99%